Anticipating Z-generation tourists’ green hotel visit intention utilizing an extended theory of planned behavior - Pan, JiaLiang; Teng, Yi-Man; Wu, Kun-Shan; Wen, Ting-Chung (Frontiers in Psychology, 2022)
Due to the effect COVID-19 epidemic, promoting green consumption is now a key marketing strategy in the hospitality and tourism industry. As it is vital green hotels predict their customers’ visit intention, this study attempts to discover the factors affecting Taiwan’s Z-generation tourists’ green hotel visit intention using an extended theory of planned behavior (including personal moral norms and environmental concern). Data was gathered from 296 Z-generation tourists via an online survey, which was subsequently analyzed using partial least squares structural equation modelling. The results evidence that Z-generation tourists’ attitude, subjective norms, and perceived behavioral control positively and significantly influence their green hotel visit intention, with attitude being the most significant factor. Moreover, the mediation model analysis indicates Z-generation tourists’ attitude toward green hotels mediates the relationships between personal moral norms, subjective norms, environmental concern, and visit intention. This study provides new insights into tourists’ green hotel visit intention and emphasizes the importance of attitude in the formation of intention.